2015
DOI: 10.4103/0970-4388.155124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perinatal oral health care education programme on the knowledge, attitude and practice behavior amongst gynaecologists of Vadodara city

Abstract: It can be concluded that there is a need for provision of education and awareness to the primary health care providers which would help in improving pregnant women and infant's oral health status along with establishment of dental home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Our findings also support earlier reports [3234, 40] about the misconceptions among ANC providers regarding oral health in pregnancy. Over half of ANC providers believed the myth that calcium will be drawn out of mothers’ teeth by the developing baby, and over a third falsely believed it is unsafe to obtain dental radiographs in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also support earlier reports [3234, 40] about the misconceptions among ANC providers regarding oral health in pregnancy. Over half of ANC providers believed the myth that calcium will be drawn out of mothers’ teeth by the developing baby, and over a third falsely believed it is unsafe to obtain dental radiographs in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally in our study, some ANC providers reported limited knowledge regarding the association between maternal oral health and early childhood caries in their infants, with less than two thirds of providers identifying this. Earlier studies have reported even lower knowledge of this association among O&Gs with less than a third of respondents identifying this link [32, 34]. …”
Section: Discussionmentioning
confidence: 99%
“… • No significant change in OH knowledge/perceptions of pregnant women between baseline and follow-up at 36 weeks • Improved OH practices (e.g. frequency of brushing and flossing teeth) and attendance for dental check-up during pregnancy • Reduced OH problems in 3rd trimester • Potential role of IHW Dental Health Services Victoria, 2017 [ 41 ] Australia Government brochure To provide culturally-appropriate information about available dental services for Aboriginal and Torres Strait Islander peoples N/A Intervention: • Free dental services for any Aboriginal or Torres Strait Islander person at the Royal Dental Hospital of Melbourne • Aboriginal Liaison Officer can assist with streamlining communication • Potential role of IHW Deshpande et al, 2015 [ 54 ] India Peer-reviewed journal article Assess the impact of the perinatal OH care education program on the knowledge, attitude & practice behaviour amongst gynaecologists Cross-sectional Program: • Flip chart and OH resource brochures provided to 46 gynaecologists • Assessed after 1 month • Significant improvement in OH knowledge ( p < 0.001), & practice behaviour ( p < 0.001) • No significant change ( p = 0.49) in attitude of respondents • Training program George et al, 2016 [ 52 ] Australia Peer-reviewed journal article Evaluate the effectiveness of the Midwifery Initiated OH (MIOH) program in improving the OH knowledge of midwives & assess their confidence to promote maternal OH post training Pre-post test Program: • Antenatal OH education and referral • 3 self-paced online modules over 3 months Delivered to 50 midwives • Significantly improved midwives’ knowledge ( p < 0.001) • At program completion 82% of respondents were confident in introducing the topic of OH in their antenatal session, 77.6% were confident with dental service referrals, and 46% were confident to undertake a visual mouth check • Training program George et al, 2016 [ 56 ] Australia Peer-reviewed journal article Undertake sensitivity and specificity assessment of the maternal OH screening tool using two comparison approaches- the Oral Health Impact Profile and a clinical oral assessment by trained study dentists Diagnostic test Screening tool: 2-Item Maternal Oral Health Screening Tool administered by midwives 1. OH status 2.…”
Section: Resultsmentioning
confidence: 99%
“…The search yielded four articles reporting training programs in promoting maternal oral health to non-dental health professionals including midwives [ 44 , 52 , 53 ] and gynaecologists [ 54 ]. Two of these studies delivered face-to-face oral health education and promotion programs [ 44 , 53 ] while the other two employed an online self-paced module [ 52 ] and written material [ 54 ] as the delivery mode of training activities. Öcek et al’s program in Turkey [ 53 ] increased oral health knowledge of midwives through a face-to-face program involving oral hygiene procedures, techniques, and eruption chronology of deciduous teeth in young children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation